The opinions of medicine faculty students about anatomy education - Turhan, Begumhan; Cetkin, Murat; Bahsi, Ilhan; Kervancioglu, Piraye (AVES PRESS LTD, 2016)
Introduction: Anatomy education known as being among the most significant components of medical education exists in the first and second semester lecture contents of medicine faculties. The considering of medicine faculty students viewpoints about anatomy education is important for improving anatomy education and teaching methods. In addition, the evaluation of interest and awareness of students to anatomy in postgraduate specialization preferences provides to predict researcher number which will be study in this area. Materials and Methods: In this study, it was proposed to evaluate the opinions of medicine faculty students about anatomy education and the view points and the awareness to anatomy in postgraduate specialization education. This study was performed on Gaziantep University second and third year medicine faculty students (n= 340). The data were obtained by feedback method with a questionnaire which consist of 30 question. Results: It was found that the students chiefly benefited from lecture notes while they have been studied to theoretical and practical part of the anatomy individually. No significant correlation was found among general average grade arid lengths of anatomy study of students (r= 0.097, p= 0.074). Fifty percent (%50) of students thought that don't use of cadaver is always a deficiency in anatomy education. It was seen that the postgraduate career preferences of the students of 39.4% was internal medicine departments. The rate of students desiring the postgraduate anatomy specialization education was 1.2%. Conclusion: In conclusion, the achieved results may will be beneficial for improving the new educational strategies related anatomy, resolving the present deficiencies and increasing the tendency to postgraduate anatomy education.
Keywords: Anatomy education; specialization preference; medicine faculty; cadaver